Analisis Keandalan dan Strategi Pemeliharaan Mesin Press Menggunakan Pendekatan OEE dan RCM di PT. XYZ - Satrio, Fabyan Hijri; Suwarno, Agus; Syahliantina, Annisa (Jurnal Teknik Industri Terintegrasi (JUTIN), 2026)
This study was motivated by recurring failures of the EP-28 press machine that potentially reduced system reliability and operational effectiveness despite a relatively high OEE value. The objective was to analyze machine reliability and effectiveness and to develop a maintenance strategy based on Reliability Centered Maintenance (RCM). This quantitative study used downtime data from April to September 2025 as the research sample. Reliability parameters, including MTBF, MTTR, availability, and OEE, were calculated, and FMEA was applied to identify critical components and root causes of failure. The results indicate an MTBF of 5,169.44 minutes, MTTR of 207.22 minutes, availability of 96.15%, and OEE of 87.94%. The most critical components were the motor drive and cylinder. The proposed strategy emphasizes condition-based maintenance and adjustment of time-based maintenance intervals to improve failure risk control and sustain machine performance.